A PLACE IN THE NUTRITION OF THE POPULATION OF UZBEKISTAN FROM NATIONAL CONFECTIONERY, “NAVAT” (World Bulletin of Public Health, 2022)
A special place in the nutrition of the population of Uzbekistan from national confectionery products is occupied by “Navat (nabat, navvat)”. Navat is a traditional sweet, common in the countries of Central Asia (Uzbekistan) and Iran. It is a crystallized sugar syrup. It has many names characteristic of different regions - navat, kinva-sugar, nabat and navot, or simply Uzbek sugar
Keywords: Uzbek sugar; Navat; crystallized; monosaccharides